PENGARUH PENDIDIKAN AKIDAH AKHLAK DALAM MEMBANGUN KARAKTER PESERTA DIDIK DI MTs AL-ISLAMIYAH DESA KARANG ANYAR KECAMATAN BERINGIN KABUPATEN DELI SERDANG - Delviana Shinta (Jurnal Bilqolam Pendidikan Islam, 2022)
This research is based on the seriousness of the students in practicing aqidah moral education both at home and in the school environment which can be seen from whether the effect of akidah moral education is in building the character of students. Then the author's goal of conducting this research is to determine the effect of aqidah moral education in building the character of students at MTs Al-Islamiyah, Karang Anyar Village, Beringin District. The research that the author is doing here is research using quantitative methods. After this research the authors conducted at MTs Al-Islamiyah Karang Anyar Village, Beringin District with a sample of 67 people and the data the authors obtained were from students using a questionnaire technique. As for the results of this research, aqidah akhlak shows a number of 32.88. The results of the standard deviation of variable X, namely education on aqeedah morals, show a number of 3.69. And the highest frequency obtained from the X variable, namely aqidah moral education with a value of 35, gets a result of 22.78% which can be said to be good. The result of the mean (average) variable y, namely the character of the students, shows a number of 31.31. And the standard deviation of the variable y, namely the character of the students, shows a number of 2.66. And the highest frequency obtained from the variable y, namely the character of students with a value of 30, gets a result of 22.11% which can be said to be sufficient. This study obtained 6.1911> 0.244, so the hypothesis was accepted, namely that there was a positive and significant influence between aqidah moral education in building the character of students at MTs Al-Islamiyah, Karang Anyar Village, Beringin District, Deli Serdang Regency.